CIRTA: A FORMAL LANGUAGE FOR MODULAR ECATNETS SPECIFICATION (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
CIRTA (''Construction Incrémentale des Réseaux de Petri à Termes Algébriques”) is aspecification language endowing ECATNets (''Extended Concurrent Algebraic Terms Nets”) [6][10]with modularity concepts to make them more suitable for real-world applications. This paperaddresses the structuring mechanisms provided by CIRTA, for the design of complex concurrentsystems. Two structuring techniques are presented. The first one relies on the usage of CIRTAmodules which extend ECATNets with the concepts of interface nodes and composed-nodes. Thesecond mechanism concerns with some structuring operations on CIRTA modules namely:importation, composition and renaming. The semantics of each CIRTA specification using theseconstructs is defined by giving the behavioral equivalent ECATNet.